NF-κB-mediated up-regulation of Bcl-x and Bfl-1/A1 is required for CD40 survival signaling in B lymphocytes - Lee, Ho H. (The National Academy of Sciences, 1999)
Activation of CD40 is essential for thymus-dependent humoral immune responses and rescuing B cells from apoptosis. Many of the effects of CD40 are believed to be achieved through altered gene expression. In addition to Bcl-x, a known CD40-regulated antiapoptotic molecule, we identified a related antiapoptotic molecule, A1/Bfl-1, as a CD40-inducible gene. Inhibition of the NF-κB pathway by overexpression of a dominant-active inhibitor of NF-κB abolished CD40-induced up-regulation of both the Bfl-1 and Bcl-x genes and also eliminated the ability of CD40 to rescue Fas-induced cell death. Within the upstream promoter region of Bcl-x, a potential NF-κB-binding sequence was found to support NF-κB-dependent transcriptional activation. Furthermore, expression of physiological levels of Bcl-x protected B cells from Fas-mediated apoptosis in the absence of NF-κB signaling. Thus, our results suggest that CD40-mediated cell survival proceeds through NF-κB-dependent up-regulation of Bcl-2 family members.